Comparative transcriptome analysis of two sugarcane varieties in response to diazotrophic plant growth promoting endophyte Enterobacter roggenkampii ED5. Issue 1 (1st January 2022) - Guo, Dao-Jun; Li, Dong-Ping; Singh, Rajesh Kumar; Singh, Pratiksha; Verma, Krishan K.; Sharma, Anjney; Qin, Ying; Khan, Qaisar; Song, Xiu-Peng; Malviya, Mukesh K.; Xing, Yong-Xiu; Li, Yang-Rui
ABSTRACT: Diazotrophic plant growth-promoting endophytic (DPGPEB) bacterium plays an important role in plant growth and development. However, the molecular mechanism of the interaction between DPGPEB and sugarcane is still less known. In this study, we used the RNA sequencing technology to compare the transcriptome of two sugarcane varieties GT11and B8 inoculated with Enterobacter roggenkampii ED5. The results showed that a total of 1905 differentially expressed genes (DEGs) were obtained in the ED5 inoculated plants as compared to the control for variety GT11, of which 812 were down-regulated and 1093 were up-regulated, respectively. Whereas, for variety B8, 6214 DEGs were detected in the ED5 inoculated plants as compared to the control, of which 1587 and 4627 of down-regulated and up-regulated, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed the DEGs were associated with starch and sucrose, nitrogen metabolism, biosynthesis of phenylpropanoid, phytohormone signal transduction, MAPK signaling pathway, secondary metabolic pathway, cell wall biogenesis, and photosynthesis. Additionally, the results of RNA-seq data were validated with qRT-PCR. In summary, these results provide valuable information about the transcriptomic changes of the two sugarcane varieties in response to E. roggenkampii ED5 for understanding the molecular mechanisms of sugarcane-bacteria interactions.